Prawns Identification in the Parit Belanda River, Rumbai Pesisir Sub-Regency, Pekanbaru, Riau - Pinem, Novalina; Putra, Ridwan Manda; ', Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Parit Belanda River is a branch of the Siak River and is inhabited by many typesof aquatic organisms, but the scientific information of those organisms is almostnone. To understand the types of prawns present in that area, a study has beenconducted from November 2015 to February 2016. There were 3 sampling areas,in the upstream (St I), the middle area (St II) and in the downstream (St III).Prawns sampling were conducted one /week for a month period, using a net(mesh size 0.5 cm) and scoop net (mesh size 0.5 cm). Morphometrical andmeristical data of the prawns were then analyzed descriptively. The prawnssampled were identified based on Cay et al. (2004) and Wowor and Choy (2001).Result shown that prawns sampled was few, there were only 30. The prawnsspecies present were consisted of 1 species only, Macrobrachium equidens Dana,1852 (Palaemonidae). This species characterized by slightly bent upward rostrum.Rostrum, propodus and telson of the male are longer than those of the female.Keywords : Macrobrachium equidens, prawn, Parit Belanda River